Perkemahan Nusantara sebagai Implementasi Projek Penguatan Profil Pelajar Pancasila Fase B Tema Bhineka Tunggal Ika - Naomi Dias Dewi; Vivi Darmayanti (Elementary Teacher Education Program, Majalengka University, 2023)
Teaching in the new Kurikulum Merdeka might be challenging for teachers who experienced learning and teaching in different eras. It is because teachers should be able to provide space and freedom for students to increase their respective potential. This research uses a qualitative approach using descriptive research methods. This paper is trying to elaborate how Kurikulum Merdeka can be facilitated through Perkemahan Nusantara in phase B in primary school. The data were gathered by means of interviews, observation, and focus discussion with elementary school teachers and the vice principals of curriculum in SD Tumbuh 1 Yogyakarta. The result of the study showed that implementing the Pancasila Student Profile Phase B were able to make students be grateful, students able to accept the differences that exist in their surrounding environment, and students were able to work together with friends and school members when carrying out assignments and discussion, also students can express ideas and opinions and show creativity in completing challenges or assignments. Further, it puts forward an activity example of the application of the project to strengthen the Pancasila Student Profile Phase B with the theme of Bhinneka Tunggal Ika through Nusantara Camp activities.